2021
DOI: 10.1002/alz.12254
|View full text |Cite
|
Sign up to set email alerts
|

Integrative functional genomic analysis of intron retention in human and mouse brain with Alzheimer's disease

Abstract: Intron retention (IR) has been implicated in the pathogenesis of complex diseases such as cancers; its association with Alzheimer's disease (AD) remains unexplored. We performed genome-wide analysis of IR through integrating genetic, transcriptomic, and proteomic data of AD subjects and mouse models from the Accelerating Medicines Partnership-Alzheimer's Disease project. We identified 4535 and 4086 IR events in 2173 human and 1736 mouse genes, respectively. Quantitation of IR enabled the identification of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…Importantly, we find reproducible alterations of specific RNA editing events in the context of AD. This is similar to our recent report of reproducible splicing alterations in AD 10 and the broader narrative of specific disruptions in RNA maturation 10 , 11 and in the epigenome in relation to AD 12 . Our list of top genes associated with AD does not overlap with that from the genetic studies of AD, and none of the RNA editing events located in the AD relevant genes reported by the genetic studies reached a genome-wide significance threshold (Table S6 ), suggesting that changes in RNA editing in AD are unlikely to be related to genetic risk factors or to affect the same targets.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, we find reproducible alterations of specific RNA editing events in the context of AD. This is similar to our recent report of reproducible splicing alterations in AD 10 and the broader narrative of specific disruptions in RNA maturation 10 , 11 and in the epigenome in relation to AD 12 . Our list of top genes associated with AD does not overlap with that from the genetic studies of AD, and none of the RNA editing events located in the AD relevant genes reported by the genetic studies reached a genome-wide significance threshold (Table S6 ), suggesting that changes in RNA editing in AD are unlikely to be related to genetic risk factors or to affect the same targets.…”
Section: Discussionsupporting
confidence: 92%
“…UPF2, as noted above, plays an important role in mRNA surveillance and the degradation of transcripts by NMD that contain premature stop codons through mutations or missplicing events. We have previously shown that aggregation of RNA binding proteins that are involved in mRNA splicing is an early event in AD pathogenesis, and likely leads to aberrant mRNA splicing events that may give rise to premature stop codons or alternative exon-exon junctions 10,38,39,[65][66][67] . These proteins, such as U1 small nuclear ribonucleoprotein 70 kDa (SNRNP70, or U1-70K) and others that are part of the U1 spliceosome complex, have been shown to interact with NFTs through their low-complexity basic-acidic domains, and were strongly enriched in the M13 RNA splicing module 68 .…”
Section: Discussionmentioning
confidence: 99%
“…However, DS genes in AD exhibited few overlaps with those previously identi ed in brain transcriptome data (Supplementary Fig. 4B-C) [31,32], highlighting the tissue-speci city of splicing events.…”
Section: Stat1 a Key Transcription Regulator Of Type I Ifn Signaling Is Differentially Spliced In Scdmentioning
confidence: 54%